Reactive Oxygen Species (ROS): Beneficial Companions of Plants’ Developmental Processes - Singh, Rachana; Singh, Samiksha; Parihar, Parul; Mishra, Rohit K.; Tripathi, Durgesh K.; Singh, Vijay P.; Chauhan, Devendra K.; Prasad, Sheo M. (Frontiers in Plant Science, 2016)
Reactive oxygen species (ROS) are continuously generated inevitably in the redox reactions of plants, including respiration and photosynthesis. In earlier studies, ROS were considered as toxic by-products of aerobic pathways of the metabolism. But in recent years, concept about ROS has changed because they also participate in developmental processes of plants by acting as signaling molecules. In plants, ROS regulate many developmental processes such as cell proliferation and differentiation, programmed cell death, seed germination, gravitropism, root hair growth and pollen tube development, senescence, etc. Despite much progress, a comprehensive update of advances in the understanding of the mechanisms evoked by ROS that mediate in cell proliferation and development are fragmentry and the matter of ROS perception and the signaling cascade remains open. Therefore, keeping in view the above facts, an attempt has been made in this article to summarize the recent findings regarding updates made in the regulatory action of ROS at various plant developmental stages, which are still not well known.